IMPROVING THE METHODOLOGY AND MECHANISM FOR STRATEGIZING THE DEVELOPMENT OF RENEWABLE ENERGY SOURCES - Sadullaeva Muslimakhon (Scholar Express Journals, 2025)
The transition from fossil fuels to clean energy sources is a major global challenge, but especially for countries with fossil fuel reserves and economies dependent on fossil fuel exports. Here, we introduce an improved framework for renewable energy planning and decision-making that will help such countries use renewable energy sources more effectively.
Keywords: Use of renewable energy; sustainable performance